Pollution and Impact of Domestic Wastewater and Industrial Wastewater on Water Resources - Hui Jiashun; Zhang Yichen; Zhu Xiaoyou (MATEC Web of Conferences)
Water resources are the core natural resources for human survival and development. In the process of rapid industrialization, the uneven distribution of water resources and pollution problems are becoming increasingly serious, threatening the ecological environment, economic development, and public health. This paper examines the current situation and impact of water pollution in China and discusses the main sources of pollution, such as industrial wastewater, agricultural non-point source pollution, and domestic sewage discharge. Through case analysis, the pollution problems and ecological damage of typical water bodies such as the Yellow River and Dianchi Lake are revealed. This paper further analyzes the threat of water pollution to the ecological environment and human health, especially the impact on public health through biological pathogen infection and chemical pollutant poisoning. Finally, this paper proposes the improvement of policies and regulations, pollution control technologies and measures, and ecological restoration solutions for water pollution, such as the promotion of Fenton oxidation and biological coupling technology, agricultural prevention and control technology, and domestic sewage treatment technology, aiming to provide theoretical support and practical guidance for water environment governance.